Improving the Education Quality by Using Blackboard System (Electronic Learning System) (Journal of the College of Basic Education, 2022)
Education, in the modern era, faces many difficulties in the different social,economical and cultural fields of life. These difficulties include the knowledge andpopulation growth, the development of the education philosophy, the change of theinstructor's role, the decreasing in the instructors' number and the development in thetechnologies and media; all these difficulties prompt specialists to take into accountthe modern educational technologies in order to solve some of the basic problems thatcolleges and education face to give all the learners proper chances in education. Thesedeveloped educational systems are not only found to access to these technologies andtheir programs, but also to create motive and stimulus environments for education.